Teaching Aids Development for Arabic Lessons to Enhance Student’s Reading Skills - Ahmad Hidayatullah Zarkasyi; Gita Hanina; Siti Anne Barkah Nur Fauziah (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
This study aims to enhance students reading skills of the ninth-grade students in Madrasah I'dadiyah Muhammadiyah. This research is research and development Borg & Gall study used to obtain a specific production, know the effectiveness of its implementation, and verify its validity for scholars, using the qualitative and quantitative approach to analyze quantitative and qualitative data. The methods used in it consisted of interviews, Tests, questionnaires, and written documents. In analyzing the data, this research used the Statistical Package for the Social Sciences, version 25 SPSS 25 method T-Test, and the Wilcoxon Signed. The developed educational aids come in the Android program by choosing the appropriate material, exercises, and teaching methods. The effectiveness is obtained from the results of the pre and post-tests by implementing: descriptive statistical analysis, conditional testing, and inferential testing in the extended experiment, and the result indicates that there is progress in their language proficiency, especially in reading skills. These teaching aids are attractive and exciting and help students learn Arabic, especially reading Arabic.